2021
DOI: 10.1002/rra.3922
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate and diatom community responses to thermal alterations below water supply reservoirs

Abstract: River impoundments have transformed river ecosystems globally due to the modification of various abiotic and biotic factors. This study provides rare evidence quantifying how water supply reservoirs alter water temperature regimes and its effects on macroinvertebrate and diatom communities over a 4‐year period. We obtained near‐continuous water temperature measurements upstream and downstream of three reservoirs and analysed thermal variables in association with macroinvertebrate and diatom community indices (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Accordingly, benthic invertebrates have been increasingly used as bioindicators since the 1950s (Beck, 1955 ), and many ecological indices based on macroinvertebrate assemblages have been developed. Such indices have been used to evaluate the effects of temperature on features of macroinvertebrate communities, for example, total taxa richness, relative proportion and/or richness of Ephemeroptera, Plecoptera and Trichoptera (EPT) (Jourdan et al ., 2018 ; Fornaroli et al ., 2020 ; Krajenbrink et al ., 2021 ), Simpson and Shannon diversity indices (Arai et al ., 2015 ) and Jaccard and Bray–Curtis indices of similarity (Burgmer, Hillebrand & Pfenninger, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, benthic invertebrates have been increasingly used as bioindicators since the 1950s (Beck, 1955 ), and many ecological indices based on macroinvertebrate assemblages have been developed. Such indices have been used to evaluate the effects of temperature on features of macroinvertebrate communities, for example, total taxa richness, relative proportion and/or richness of Ephemeroptera, Plecoptera and Trichoptera (EPT) (Jourdan et al ., 2018 ; Fornaroli et al ., 2020 ; Krajenbrink et al ., 2021 ), Simpson and Shannon diversity indices (Arai et al ., 2015 ) and Jaccard and Bray–Curtis indices of similarity (Burgmer, Hillebrand & Pfenninger, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, inter‐basin transfer schemes between impounded systems can alter the thermal dynamics of rivers depending on the size and T w regimes of the donor and receiving waterbodies. For instance, Krajenbrink et al (2022) found that a water transfer scheme reversed the summer cooling effect of a reservoir as the donor basin yielded warmer water temperatures, thus elevating daily mean T w values by 5°C during a non‐drought summer; although evidence on the implications of such inter‐basin water transfer schemes on T w is limited globally.…”
Section: Human Influences Affecting River Water Temperature During Dr...mentioning
confidence: 99%
“…There remains a fundamental lack of understanding on how different reservoir properties collectively govern T w , including during drought conditions where flow releases could exacerbate of mitigate thermal peaks (Cowx et al, 1987). Various studies from Cfb climates have reported a thermal 'compressing' effect of water supply reservoirs on annual T w ranges, whereby summer discharges specifically are cooled by continuous compensation flow releases that restrict the occurrence of extreme low-flows and thus thermal peaks (Krajenbrink et al, 2022;Webb & Walling, 1993, 1997, although such trends are inconsistent.…”
Section: Flow Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Water temperature data were downloaded and a linear interpolation between consecutive measurements was performed to obtain a continuous series of the water temperature (one value per minute) and lastly the daily mean, maximum and minimum values. When water temperature data were lacking due to sensor failure or loss ($30% of the data) the values were estimated separately for each site from air temperature by Generalized Additive Models (GAM) using daily water temperature (mean, maximum, and minimum) and air temperature (mean) time series plus the week number as an extra smoothing parameter (see Krajenbrink et al (2021) for details) to have a continuous data set. GAMs were developed by "mgvc" (Wood, 2022) R package using a Gaussian distribution and provided an excellent performance (Root Mean Square Error [RMSE] $0.82 C, see Table 1A).…”
Section: Study Areamentioning
confidence: 99%